Power Relations in Mangrove Ecosystem Management: The Authority of Kotawaringin Village Government Amid Environmental Policy Structures - Nur Aysyah; Zalfa Haza Tsabitah; Nyimas Dwi Febyana (Pencerah, 2026)
This study aims to analyze power relations in mangrove ecosystem management in Kotawaringin Village, Bangka Regency, with a focus on the position and authority of the village government within a hierarchical environmental policy structure. The research employs a qualitative approach using a political ecology perspective to examine the dynamics of power among actors in mangrove governance. Data were collected through in-depth interviews, field observations, and document analysis involving village authorities, coastal communities, and relevant policy documents. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that, normatively, the village government is recognized as an autonomous entity within the decentralization framework; however, substantively, its authority is constrained by supravillage policies at the regency and provincial levels. This condition produces hierarchical power relations that position the village government in a subordinate role. Furthermore, a paradox of responsibility emerges, where the village is expected to ensure mangrove sustainability without adequate regulatory authority. The study concludes that mangrove management at the village level constitutes a political arena shaped by power distribution, requiring more inclusive policies, strengthened local institutional capacity, and more equitable coordination among governance actors in coastal environmental management.